Sorting out the Florida Sabal Palms - David A. Fox; Michael G. Andreu (EDIS)
While traveling through the Florida peninsula, a casual observer will notice a wide variety of palms and find that many are called “palmetto.” This 4-page fact sheet helps field investigators identify the four Sabal species found in Florida's natural areas, first by distinguishing them from other fan palms and then from each other. Written by David A. Fox and Michael G. Andreu, and published by the UF Department of School of Forest Resources and Conservation, March 2012.